Oxford Handbook of Philosophy and Disability - Cureton, Adam; Wasserman, David (Oxford University Press, 2018)
This Handbook introduces philosophers, as well as other scholars in the humanities and social sciences, to one of the most dynamic new areas of philosophical inquiry. Disability raises some of the deepest conceptual and normative issues about human embodiment and well-being; dignity, respect, justice and equality; and personal and social identity. But it also raises pressing practical questions for educational, health, reproductive, and technology policy, and confronts controversial questions about the scope and direction of the human and civil rights movements. The Handbook addresses these issues and more, with contributions from some of the most prominent philosophers in the field. The clarity it brings to these discussions demonstrates fully the continued centrality and importance of philosophical inquiry.